1991
DOI: 10.1016/0304-3959(91)90031-r
|View full text |Cite
|
Sign up to set email alerts
|

Health locus of control beliefs and psychological distress as predictors for treatment outcome in low-back pain patients: results of a 3-month follow-up of a controlled intervention study

Abstract: Association of health locus of control beliefs (HLC) and psychological distress (GHQ-12) with short-term outcome of low-back pain (LBP) rehabilitation was studied in patients with chronic or recurrent LBP (n = 459; aged 35-54 years; 63% men). These patients were randomly assigned to 3 study groups, namely the inpatient, the outpatient and the control group. The results showed a significant decrease in disability due to LBP in the 2 treated groups; in addition, the accomplishment and frequency of back exercises… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
66
1
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(76 citation statements)
references
References 26 publications
7
66
1
2
Order By: Relevance
“…The sustained but limited long-term decrease in functional disability and depression is consistent with the findings of other studies of multidisciplinary pain treatment strategies (1,39,40). In another study involving the same patient sample (Samwel et al, submitted), we found that functional disability and depression also significantly decreased immediately after treatment in comparison to a waiting list control group, as was the level of pain; however, unlike the effects of treatment on functional disability and depression, the effect of treatment on pain was not sustained during the 12-month follow-up.…”
Section: Discussionsupporting
confidence: 86%
“…The sustained but limited long-term decrease in functional disability and depression is consistent with the findings of other studies of multidisciplinary pain treatment strategies (1,39,40). In another study involving the same patient sample (Samwel et al, submitted), we found that functional disability and depression also significantly decreased immediately after treatment in comparison to a waiting list control group, as was the level of pain; however, unlike the effects of treatment on functional disability and depression, the effect of treatment on pain was not sustained during the 12-month follow-up.…”
Section: Discussionsupporting
confidence: 86%
“…Patients with chronic or recurrent LBP who relied on others, i.e. patients with a high external locus of control, also seem to use more passive coping strategies, such as hoping and praying, but also catastrophizing (15,16). Some participants in category (i) also mentioned a sense of guilt and selfaccusation.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers (Crisson & Keefe, 1988) have shown that individuals with pain and a high perceived control trust that their own actions can affect the future course of the pain and they build up effective strategies for dealing with pain, and thus they report a lower pain intensity. Moreover, previous studies (Härkäpää, Järvikoski, Mellin, Hurri, & Luoma, 1991;Turner & Clancy, 1986) have demonstrated that individuals with low perceived control rely more on ineffective coping strategies. They report a poor ability to control and decrease their pain, they do not believe in recovery, and they avoid increasing their activity level.…”
Section: Discussionmentioning
confidence: 99%